2011
DOI: 10.2298/jas1103197b
|View full text |Cite
|
Sign up to set email alerts
|

Management of stem borers on some quality protein maize varieties

Abstract: Four Quality Protein Maize (QPM) varieties: Dent, Sakatifu, Flint, Sammaz 14 and TZEE (Local Check) were evaluated for their response to stem borers. Furadan 3G was applied at the rate of 20 kg/ha at planting for the control of the stem borers. The stem borers damage was assessed by determining the number of leaves with ‘windows’ and plants with ‘deadhearts’. The number of exit holes and tunnels on the stem were also determined and the tunnel length measured. Varieties Dent and Sakatifu had more windows,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Among the five different maize cultivars, it was noticed that 'Ronimi' was the affected cultivar; this might be due to the cultivars morphological character like compact whorl, soft stem and long internodes. This is in agreement with Bamaiyi and Joan (2011).…”
Section: Stem Tunnelingsupporting
confidence: 93%
“…Among the five different maize cultivars, it was noticed that 'Ronimi' was the affected cultivar; this might be due to the cultivars morphological character like compact whorl, soft stem and long internodes. This is in agreement with Bamaiyi and Joan (2011).…”
Section: Stem Tunnelingsupporting
confidence: 93%
“…These results corroborate with those of Ramkumar and Tanweer Alam (2017) on the efficacy of chlorantraniliprole and carbofuran in maize. Bamaiyi and Joan (2011) observed that the tunnel damage was relatively less in carbofuran 3G treated plots as observed now. The exit holes caused by the adult emergence were less in chlorantraniliprole 18.5SC (1.8) followed by spinosad (1.9) and chlorantraniliprole 0.4G (2.3) Ramkumar and Tanweer Alam (2017).…”
Section: Resultssupporting
confidence: 77%
“…Population of pest insects living in an environment where some habitats are occasionally destroyed may achieve its maximal growth rate when they spread the risk of local extinction (Yoshimura and Jansen 1996;Jansen and Yoshimura 1998;Maslov and Sneppen 2015b). Stem borers are usually serious pests in farmlands (Hoffmann and Frodsham 1993;Sun et al 1993;Rahman et al 2004;Bamaiyi and Joan 2011). These pests are considered to be pure pests, because they do not use wild substitute host plants.…”
Section: Discussionmentioning
confidence: 99%